Identification of mathematical model of diesel fuel hydrotreatment process for creation system optimization of group of technological units of oil refinery plant - R. A. Khakimov (Омский научный вестник)
The article deals with the dynamic optimization of complex technological processes on the example of the process of hydrotreating of diesel fuel. The purpose of the study is to create a system of optimization of a group of technological installations in real time. The relevance of the study is determined by the fact that the existing optimal control systems solve the problem of local optimization of one process, rather than the problem of global optimization of oil refinery chains. There is also a problem of lack of integration solutions between the optimal planning systems and control systems of technological installations. As an integration system, it is proposed to use the system of optimization of a group of technological installations in accordance with the hierarchy of refinery management systems, discussed in this article. In the framework of the study, the identification of the technological process to obtain a mathematical model of several plants of different capacity using regression analysis methods of historical data. The model has been evaluated with statistical estimates and meets the requirements of accuracy and adequacy. As a result of the study, a mathematical model of hydrotreatment is developed to solve the problem of minimizing energy consumption while respecting product quality restrictions. The quality of the obtained model confirms that the creation of a system for optimization of a group of technological units in real time is possible, and the model can be used in dynamic optimization of the production chain of diesel fuel.